Optimal incentives in a principal-agent model with endogenous technology - Marco A. Marini; Paolo Polidori; Désirée Teobaldelli; Davide Ticchi (Games, 2018)
One of the standard predictions of the agency theory is that more incentives can be given to agents with lower risk aversion. In this paper, we show that this relationship may be absent or reversed when the technology is endogenous and projects with a higher efficiency are also riskier. Using a modified version of the Holmstrom and Milgrom's framework, we obtain that lower agent's risk aversion unambiguously leads to higher incentives when the technology function linking efficiency and riskiness is elastic, while the risk aversion-incentive relationship can be positive when this function is rigid.
Keywords: D21; D81; D82; D86; M52; O33; 330; principal-agent; incentives; risk aversion; endogenous technology